Rational Design of π-Conjugated Tricoordinated Organoboron Derivatives With Thermally Activated Delayed Fluorescent Properties for Application in Organic Light-Emitting Diodes - Jin, Ruifa; Xin, Jingfan (Frontiers in Chemistry, 2020)
A series of donor−acceptor (D−A) tricoordinated organoboron derivatives (2–10) have been systematically investigated for thermally activated delayed fluorescent (TADF) based organic light-emitting diodes (OLEDs) materials. The calculated results show that the designed molecules exhibit small singlet-triplet energy gap (ΔEST) values. Density functional theory (DFT) analysis indicated that the designed molecules display efficient separation between donor and acceptor fragments because small overlap between donor and acceptor fragments on HOMOs and LUMOs. Furthermore, the delayed fluorescence emission color can be tuned effectively by introduction of different polycyclic aromatics fragments in the parent molecule 1. The calculated results show that molecules 2, 3, and 4 possess more significant Stokes shifts and red emission with small ΔEST values. Nevertheless, other molecules exhibit green (1, 7, and 8), light green (6 and 10), and blue (5 and 9) emissions. Meanwhile, they are potential ambipolar charge transport materials except 4 and 10 can serve as electron and hole transport materials only, respectively. Therefore, we proposed a rational way for the design of efficient TADF materials as well as charge transport materials for OLEDs simultaneously.